Morphological Interference in Agak Laen Movie by Muhadkly Acho - Endang Wiyanti (CV. Rustam, 2025)
This article examines the form of morphological interference found in the movie Agak Laen by Muhadkly Acho. This research aims to analyze morphological interference, the influence of regional language interference on morphological structure in film dialogue, and the factors behind its use. This research uses a descriptive qualitative approach. The data collection technique in this research uses the documentation method, focusing on the conversation text in the movie. Data analysis was conducted through content analysis. In this study, it is found that the morphological interference that appears most dominant is in the form of the use of affixation which has changed, even omitted. Besides affixation, morphological interference is also found in the form of reduplication, especially in the form of affixed rewords. Meanwhile, there is no morphological interference in the form of compound words. The interference that appears in the dialogs of this film is mostly influenced by the local dialect variations used by the characters, such as the influence of Eastern, Malay, and North Sumatra dialects. The interference also plays a role in enriching the characters, creating an atmosphere of humor, and reflecting the diversity of the Indonesian language. The use of local language variations such as Malay and other local dialects not only gives color to the characters but also brings the audience closer to the existing social reality. The results of the analysis show that morphological interference in this movie strengthens cultural identity and local characters in the context of visual communication.